Estimation of Breeding Values by Various Sire Evaluation Methods for Selection of Sires in Crossbred Cattle - Shashikant; Singh, C. V.; Barwal, R. S.; Sarma, Olympica (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted from January to November, 2022 at G.B. Pant University of Agriculture and Technology, Pantnagar, with the objective of ranking sires based on first lactation traits. The breeding values of 66 crossbred sires were evaluated for age at first calving, first lactation length, and first lactation milk yield using Best Linear Unbiased Prediction, Least Squares Method, and Restricted Maximum Likelihood methods. The average breeding values for age at first calving were 1153.41 days (Best Linear Unbiased Prediction), 1152.25 days (Least Squares Method), and 1153.93 days (Restricted Maximum Likelihood); for first lactation length, 340.51 days (Best Linear Unbiased Prediction), 353.24 days (Least Squares Method), and 354.04 days (Restricted Maximum Likelihood); and for first lactation milk yield, 3348.81 kg (Best Linear Unbiased Prediction), 3602.34 kg (Least Squares Method), and 3612.37 kg (Restricted Maximum Likelihood). Significant and highest Spearman's rank and Pearson correlation coefficients were observed between LSM and REML for the first lactation length and milk yield, indicating that these methods were highly correlated and equally accurate for ranking sires. Sire no. 15 showed consistently high breeding values for age at first calving across all methods, securing the top rank for this trait. For the first lactation length, sire no. 23 ranked first with BLUP, while sire no. 59 led in LSM and REML. Different sires topped the rankings for first lactation milk yield in each method. Overall, 4–5% of top-ranked sires maintained similar ranks across evaluation methods, providing insights into sire performance.